2015
DOI: 10.4149/bll_2015_115
|View full text |Cite
|
Sign up to set email alerts
|

Can a single lactate value predict adverse outcome in critically ill newborn?

Abstract: OBJECTIVES: The aim of this study was to investigate the role of the lactic acidosis, as an early predictor of signifi cant consequences and/or a fatal outcome in term neonates after a perinatal asphyxia. BACKGROUND: Severe perinatal asphyxia can generate multiple organ dysfunction and neonatal mortality. METHODS: In routine clinical practice, after an admission to the Intensive Care Unit, lactate concentration was determined in capillary blood samples during the fi rst one to six hours after birth in 55 term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…These results were in line with some studies which found that serum lactate level was higher in hypoxic neonatal group than healthy one (Gasparović et al, 2012;Simovic et al, 2015). Also, the study of Chiang et al (2016) revealed that higher serum lactate in hypoxic neonates and higher level was found in grade III HIE.…”
Section: Discussionsupporting
confidence: 90%
“…These results were in line with some studies which found that serum lactate level was higher in hypoxic neonatal group than healthy one (Gasparović et al, 2012;Simovic et al, 2015). Also, the study of Chiang et al (2016) revealed that higher serum lactate in hypoxic neonates and higher level was found in grade III HIE.…”
Section: Discussionsupporting
confidence: 90%
“…The different policies between hospitals and departments reflect the controversy regarding the usefulness of the blood sample (1). Lately, interesting papers about blood lactate level as a predictor of clinical outcomes have been published, but if we consider the whole literature scenario we do not have enough data to consider lactate a totally reliable prognostic index, or at least not in all the clinical settings (2)(3)(4)(5)(6)(7)(8). Lactic acid is normally considered a molecule with an excellent sensitivity for the cellular damage caused by anaerobiosis due to an oxygen debit during a shock status.…”
mentioning
confidence: 99%
“…25 In newborn infants with perinatal hypoxia, lactate levels >8.7 mmol/L were associated with hypoxicischemic encephalopathy (HIE) of grade $2. 21 In a prospectively managed cohort of patients with neonatal respiratory disease supported with ECLS, peak lactate >15 mmol/L was associated with the composite adverse outcome: death from any cause before 18-to 24-month follow-up or evidence of neurologic disability at 18 to 24 months. 23 Informed by studies revealing gradation of association with poor outcomes, we included lactate 3 to <5 mmol/L (nonsevere) and lactate $5 mmol/L (severe), in association with another abnormal criteria, for the definition of cardiovascular dysfunction in critically ill children.…”
Section: Biomarkers Of Cardiovascular Dysfunctionmentioning
confidence: 96%
“…Laboratory 19,20,[22][23][24] reported as maximum during a given time frame, 21 or expressed as clearance of lactate burden over time. 20 Studies have consistently revealed lactate <2 mmol/L to be an important negative predictor of mortality, whereas higher lactate levels (>3 mmol/L, >4 mmol/L, >5 mmol/L, >5.5 mmol/L, >10 mmol/ L, and >25 mmol/L) were associated with mortality, with a relatively linear relationship when multiple cutoffs were assessed in the same analysis.…”
Section: Biomarkers Of Cardiovascular Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation